Empowering the public or maintaining the hold of state control? A critical examination of the role of The Straits Times in Singapore today. - Ho, Bernard Tjin Charn. (2008)
Examines the role played by The Straits Times today as Singapore’s leading English language daily. Questions whether the newspaper is empowering the reading public at large by providing views that differ from the views of the Singapore Government or if it is increasing the hold of state control by merely appearing to offer alternative views.